The Distributional of Impacts of Cigarette Taxation in Bangladesh - Del Carmen, Giselle (World Bank, Washington, DC, 2018)
Despite the obvious positive health impacts of tobacco taxation, an argument raised against it is that poor households bear the burden of the increased prices because of their higher share of spending on tobacco. This report includes estimates of the distributional impacts of price rises on cigarettes under various scenarios using the Household Income and Expenditure Survey (HIES) 2016/17. One contribution of this analysis is to quantify the impacts by allowing price elasticities to vary across consumption deciles. This shows that an increase in the price of cigarettes in Bangladesh has small consumption impacts and does not significantly change the poverty rate or consumption inequality. These findings stem from relatively even cigarette consumption patterns between less and more welloff households. These results hold even if one considers some small substitution through the use of bidis, which are largely consumed by the poor. The short-term consumption impacts are also negligible compared with the estimated gains because of savings in medical costs and the greater number of productive years of life.